Active herpesviruses are associated with intensive care unit (ICU) admission in patients pulmonary infection and alter the respiratory microbiome - Liu, Zhiguang; Qi, Chun-jian; Shi, Yujia; Li, Tianyu; Fang, Yuan; Zhang, Qian (Frontiers in Microbiology, 2024)
Background The Herpesviridae family contains several human-related viruses, which are able to establish colonizing and latency in the human body, posing a significant threat to the prognosis of patients. Pulmonary infections represent one of the predominant infectious diseases globally, characterized by diverse and multifaceted clinical manifestations that have consistently attracted clinician’s concern. However, the relationship of herpesviruses on the prognosis of pulmonary infections and the respiratory microbiota remains poorly understood. Methods Here, we retrospectively analyzed respiratory samples from 100 patients with pulmonary infection detected by metagenomic next-generation sequencing (mNGS). Results Employing mNGS, five herpesvirus species were detected: Human alphaherpesvirus 1 (HSV-1), Human gammaherpesvirus 4 (EBV), Human betaherpesvirus 5 (CMV), Human betaherpesvirus 7 (HHV-7), and Human betaherpesvirus 6B (HHV-6B). Regression analysis showed that the age and positivity of herpesviruses in patients were independently correlated with ICU admission rates. In addition, positivity of herpesvirus was related with increased ICU days and total hospital stay. The herpesvirus-positive group demonstrated markedly higher incidences of co-infections and fungi-positive, predominantly involving Pneumocystis jirovecii and Aspergillus fumigatus. Analysis of respiratory microbiota revealed a substantially altered community composition within the herpesvirus-positive group, and herpesviruses were significantly positively correlated with the diverse respiratory opportunistic pathogens. Conclusion Overall results substantiate that the active herpesviruses in patients with pulmonary infections were significantly associated with high ICU admission rate. Moreover, the herpesviruses promotes the dysbiosis of the respiratory microbiota and an increased proportion of co-infections. These insights could contribute to unraveling the underlying mechanisms connecting active herpesviruses to the progression of severe illnesses.